EP869 Treatment of ovarian cancer in Germany from 2004–2016: results of a nationwide quality assurance program (QS Ovar). (1st November 2019) - Harter, P; Pfisterer, J; Hilpert, F; Sehouli, J; Lamparter, C; Kerkmann, M; du Bois, A
Abstract : Introduction/Background: Treatment of patients with ovarian cancer needs specialized skills and infrastructure. Longitudinal treatment characteristics in Germany are so far unknown at a national level. Methodology: All German hospitals treating patients with ovarian cancer were asked to document all patients with first diagnosis in the third quarter in 2004, 2008, 2012, and 2016. Details of tumor, treatment and outcome were documented. This analysis is focusing on patients with AOC (advanced ovarian cancer) FIGO III/IV and the endpoint 2Y-PFS (year-progression free survival) (OS data immature for 2016 cohort). Results: In 2016, QS Ovar included 65% of all patients in Germany treated in 244 hospitals. 2522 of 3512 (71.8%) documented patients have AOC. The rate of complete resection has improved from 33.3% in 2004 to 50.7% in 2016 and the application of platinum + taxane from 83.1 to 89.9%. The additional application of bevacizumab was 54% in 2012 and 67.3% in 2016. The median PFS in patients with complete resection was 26.7 months versus 16.1 months for RD (residual disease) 1–10 mm and 11.1 months for RD >10 mm (p<0.001). The 2Y-PFS of all pts was 36.3%. The 2Y-PFS increased in patients with RD >1 cm from 11.3 to 31.3% and from 27.6% to 40.5% in RD 1–10 mm. An increase in 2Y-PFS was also seen in patients with complete resection from 44.8% to 61.8%. Conclusion: QS Ovar provides representative data of the treatment of patients with ovarian cancer in Germany. Increasing rates of successful surgery and use of standard systemic treatment are associated with an increased 2Y-PFS in all subgroups of patients with advanced OC, but further potentially responsible factors should also be discussed (e.g. centralization). Mature OS data are expected in about 2 years. Disclosure: QS Ovar was supported by Amgen, Astra Zeneca, Boehringer Ingelheim, Essex, Roche. Harter: Honoraria: Astra Zeneca, Roche, Sotio, Tesaro, Stryker, ASCO, Zai Lab, MSD Advisory Board: Astra Zeneca, Roche, Tesaro, Lilly, Clovis, Immunogen, MSD/Merck; Research funding (Inst): Astra Zeneca, Roche, GSK, Boehringer Ingelheim, Medac, DFG, European Union, DKH, Tesaro, Genmab Pfisterer: Honoraria: Roche, Astra Zeneca, Tesaro, Amgen, Clovis, MSD; Advisory Board: Roche, Astra Zeneca, Tesaro, Clovis, MSD; Travel: Roche, Tesaro; Research funding: Roche, Tesaro Hilpert: Honoraria: Astra Zeneca, Clovis, Roche, Tesaro, MSD, PharmaMar, Pfizer, Novartis; Advisory Board: Astra Zeneca, Roche, Tesaro, Clovis, MSD, PharmaMar Sehouli: Honoraria: PharmaMar, Clovis, Tesaro, Roche, Astra Zeneca, Advisory Board: PharmaMar, Clovis, Tesaro, Roche, Roche Diagnostics, Astra Zeneca, Merck, Bayer, Eisei, Johnson and Johnson, MSD, Novocure, Amgen, Lilly; Research funding (Inst): PharmaMar, Clovis, Tesaro, Roche, Astra Zeneca, Medimmune, Bristol Myers, Lilly; Travel: PharmaMar, Clovis, Tesaro, Roche, Astra Zeneca Lamparter and Kerkmann: nothing to disclose du Bois: Advisory Board: AstraZeneca, Roche, Tesaro, Clovis, BioCad, Genmab, and Pfizer.